Using Relevance Theory to Enhance Students’ Pragmalinguistic and Sociopragmatic Competencies in Translation: A Theoretical Perspective - Amine, Driss Mohamed (Dirasat: Human and Social Sciences, 2024)
Objectives: This study investigates the vital role Relevance Theory plays in promoting the pragmatic competence of students in translation. It seeks to probe into the pragmalinguistic and sociopragmatic outputs as they shape the pragmatic competence, by and large, adjust the learners’ understanding of source texts, and impact their translational performances. Methods: Through some clearly-defined and context-based examples, this study adopts a descriptive-analytical method and embraces a comparative stylistic approach to answer mainly a onefold question: How effective is the use of Relevance Theory in enhancing students' pragmalinguistic and sociopragmatic competencies, and in maintaining smooth intercultural communication? This tangibly makes translation, with its intricate nature in theory and practice alike, concerned since the linguistic and metalinguistic aspects interweave in it, at which the translator’s linguistic competence displays pragmalinguistics while the metalinguistic competence mirrors sociopragmatics. Results: The study yields multiple findings, the most prominent of which is that the door should be wide open for Relevance Theory to get into the translating process by providing learners with the solutions that make both their thinking and acting pertinent to the target language communicative situation/setting. Conclusions: Thus, Relevance Theory becomes a crucial benchmark for evaluating learners' comprehensive understanding of translation prerequisites, identifying their shortcomings in conceptualization and composition, and pinpointing their urgent language usage and application needs.